ANTIMICROBIAL ACTIVITY OF THE BIODIESEL PLANT, JATROPHA CURCAS L. - K.KALIMUTHU; S.VIJAYAKUMAR; R.SENTHILKUMAR (International Journal of Pharma and Bio Sciences, 2010)
As a measure of testing the medicinal properties of Jatropha curcas, methanol extract obtained from both in vivo leaf and leaf derived callus were subjected to antimicrobial activity against six microorganisms, of the six different concentrations tested, the in vitro leaf callus extracts of at high concentrations (1.0 and 1.2%) inhibited the growth of Staphylococcus aureus and Pseudomonas sp. at maximum extend (20 and 23mm diameter in inhibition ) The antifungal activities of the leaf extract in vivo was noteworthy . However, the methanol extract of leaf derived callus of Jatropha curcas showed higher antifungal activity with concominant increase in concentrations.